2015
DOI: 10.1136/archdischild-2015-308765
|View full text |Cite
|
Sign up to set email alerts
|

Presentation of childhood cancers to a paediatric shared care unit

Abstract: The majority of children diagnosed with cancer present via acute services, with the route varying between tumour types. Only two cases in 10 years were referred via the 2-week pathway, thus challenging its relevance in the paediatric population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 10 publications
1
10
1
1
Order By: Relevance
“…Compared to previous case-only studies [9][10][11] in which confounding by time-related factors such as age or season cannot be ruled out, we were able to demonstrate relative rates of presentations compared to both case baseline and matched controls. The stable rates of healthcare access over time in the matched controls suggested that our estimates were unlikely to be largely confounded by time-related factors.…”
Section: Discussioncontrasting
confidence: 80%
See 3 more Smart Citations
“…Compared to previous case-only studies [9][10][11] in which confounding by time-related factors such as age or season cannot be ruled out, we were able to demonstrate relative rates of presentations compared to both case baseline and matched controls. The stable rates of healthcare access over time in the matched controls suggested that our estimates were unlikely to be largely confounded by time-related factors.…”
Section: Discussioncontrasting
confidence: 80%
“…corresponding numbers are listed in Supplementary Appendix I (pp. [6][7][8][9][10][11]. Among the six general presentations examined, rates of haematological presentations, musculoskeletal presentations, and injuries were the earliest to increase significantly compared to controls, which were found to increase since the third month (61-90 days) before the date of lymphoid leukaemia diagnosis ( Fig.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…Literature on the nature and frequency of symptoms experienced by adolescents and young adults before cancer diagnosis is sparse; study populations often exclude those older than 16 years. 20 , 25 , 26 Most existing studies 6 , 19 , 27 on adolescents and young adults are based on information captured in EHRs. In comparison, our findings based on self-reported data indicate substantially higher frequencies of presenting symptoms among adolescent and young adults before cancer diagnosis.…”
Section: Discussionmentioning
confidence: 99%